Using Patient-Reported Outcome Measures to Evaluate Care for Patients With Inflammatory Chronic Rheumatic Disease - Rodrigues, D (2022)
Objectives: Few countries integrate patient-reported outcome measures (PROMs) in routine performance assessment and those that do focus on elective surgery. This study addresses the challenges of using PROMs to evaluate care in chronic conditions. We set out a modeling strategy to assess the extent to which changes over time in self-reported health status by patients with inflammatory chronic rheumatic disease are related to their biological drug therapy and rheumatology center primarily responsible for their care. Methods: Using data from the Portuguese Register of Rheumatic Diseases, we assess health status using the Health Assessment Questionnaire-Disability Index for rheumatic patients receiving biological drugs between 2000 and 2017. We specify a fixed-effects model using the least squares dummy variables estimator. Results: Patients receiving infliximab or rituximab report lower health status than those on etanercept (the most common therapy) and patients in 4 of the 26 rheumatology centers report higher health status than those at other centers. Conclusions: PROMs can be used for those with chronic conditions to provide the patient's perspective about the impact on their health status of the choice of drug therapy and care provider. Care for chronic patients might be improved if healthcare organizations monitor PROMs and engage in performance assessment initiatives on a routine basis.